Seasonal Predictability of the Winter North Atlantic Oscillation From a Jet Stream Perspective - Tess Parker; Tim Woollings; Antje Weisheimer; Chris O'Reilly; Laura Baker; Len Shaffrey (Geophysical Research Letters)
Abstract The winter North Atlantic Oscillation (NAO) has varied on interannual and decadal timescales over the last century, associated with variations in the speed and latitude of the eddy‐driven jet stream. This paper uses hindcasts from two operational seasonal forecast systems (the European Centre for Medium‐range Weather Forecasts's seasonal forecast system, and the U.K. Met Office global seasonal forecast system) and a century‐long atmosphere‐only experiment (using the European Centre for Medium‐range Weather Forecasts's Integrated Forecasting System model) to relate seasonal prediction skill in the NAO to these aspects of jet variability. This shows that the NAO skill realized so far arises from interannual variations in the jet, largely associated with its latitude rather than speed. There likely remains further potential for predictability on longer, decadal timescales. In the small sample of models analyzed here, improved representation of the structure of jet variability does not translate to enhanced seasonal forecast skill.